Genetic testing for RAD51C mutations: in the clinic and community. (7th January 2015) - Sopik, V.; Akbari, M.R.; Narod, S.A.
<x xml:space="preserve">Abstract</x> Much of the observed familial clustering of breast and ovarian cancer cannot be explained by mutations in BRCA1 and BRCA2. Several other cancer susceptibility genes have been identified, but their value in routine clinical genetic testing is still unclear. Germline mutations in RAD51C have been identified in about 1% of hereditary breast and ovarian cancer families. RAD51C mutations are predominantly found in families with a history of ovarian cancer and are rare in families with a history of breast cancer alone. RAD51C is primarily an ovarian cancer susceptibility gene. A mutation is present in approximately 1% of unselected ovarian cancers. Among mutation carriers, the lifetime risk of ovarian cancer is approximately 9%. The average age at onset is approximately 60 years; this suggests that preventive oophorectomy can be delayed until after natural menopause. Under current guidelines, genetic testing for RAD51C is expected to have a limited impact on ovarian cancer incidence at a population level. This is because the penetrance is 9% to age 80; the great majority of families with mutations would be represented by a single case of ovarian cancer, these are potentially preventable through population screening but not through screening of established ovarian cancer families.